Bird's-eye view of prevalence, mechanism of injury, and prevention of sports-related orofacial injuries in basketball game - Riddhi Joshi; Krutarth Kshirsagar (Wolters Kluwer Medknow Publications, 2024)
Sports-associated orofacial trauma causes negative sequelae in an athlete. To prevent this, we must closely assess the mechanism as well as the available literature regarding the prevalence. It is easier to apply knowledge of sports dentistry if the injury mechanism, types of injury, and management are known. Every single game is accompanied by its own set of injuries. Basketball is a dynamic game. Athletes involved in this game are at high risk of orofacial injuries. The preventive aspect is often a blind spot, especially in Indian Sports. This review gives a bird's-eye view of the type of orofacial trauma and prevention in athletes playing basketball game.